Animal teachers - Halfmann, Janet (Blue Apple Books, 2014)
"What's a great way for kids to learn about learning? Tell them how an otter takes swimming lessons, or how a chick learns to peck! Short entries portray how twelve different animals are taught various "lessons." Loads of information about nature is offered in brief, kid-friendly explanations paired with striking illustrations"--